Sustentabilidade socioambiental e a saúde nos territórios (re)construídos por projetos hidrelétricos na Amazônia: o caso de Belo Monte. - Missifany Silveira; Mario Diniz de Araújo Neto; Helen Gurgel; Laurent Durieux (Confins)
This article presents a discussion of the issues inherent in the decisions that interfere with environmental sustainability and the health of populations across the impact with the implementation of hydropower in the Brazilian Amazon. From the case of the Belo Monte hydroelectric dam, one can observe how the process of environmental licensing in Brazil is based on the control and mitigation of impacts of a project by isolating social aspects, without considering the specificities of the local people. The construction of hydroelectric power plants, which occupies large territorial extensions, transfers the damage to the most vulnerable social groups as coastal communities and ethnic communities. This study points to the need for effective planning for the use of natural resources, as well as actions in the region to mitigate the main conflicts. Regarding this case, development policies without the participatory process, when implemented de-structure the logic of local organization, increasing the environmental and social problems in the area, causing repercussions on the health and quality of life. By concluding, to face these kinds of problems and challenges, as, that involve dam construction, it is necessary a wide process of participation, with an expanded view and integration of public policies on health, environment, and ethics of the development.